Properties of 12-Year Low Thinning Teak Wood for Furniture Production of Communities in Thailand - Sirisyos Kijmongkolvanich; Somchai Sevisat; Songwut Egwutvongsa (My University, 2023)
The objectives of this research were to study the physical properties of 12-year-old split teak wood and to determine the structural equation model of the utilization of 12-yearold teak by testing the mechanical properties of the wood with techniques from Thai folk wisdom as follows: 1) raw wood, 2) baked wood, and 3) wood soaked in water and dried in the sun, in order to measure the modulus of rupture (MOR) and modulus of elasticity (MOE) values for all three techniques.Moreover, the strength of the wood can be enhanced in order to support the weight by using the technique of soaking the teak wood in water and drying it in the sun.Thus, it can help to effectively reduce production costs as a method that is suitable for the climate of northern Thailand based on four factors: 1) Product Knowledge, 2) Policy and Social Requirements, 3) Material, and 4) Production Procedure by promoting the use of teak in the community in order to demonstrate good environmental friendliness.
Keywords: Thinning; Woodworking; Wood Treatment and Properties